2019
DOI: 10.1111/desc.12809
|View full text |Cite
|
Sign up to set email alerts
|

Monolingual but not bilingual infants demonstrate racial bias in social cue use

Abstract: Bilingualism exerts early and pervasive effects on cognition, observable in infancy.Thus far, investigations of infant bilingual cognition have focused on sensitivity to visual memory, executive function, and linguistic sensitivity. Much less research has focused on how bilingualism impacts processing of social cues. The present study sought to investigate whether bilingualism modulates the expression of one aspect of social processing: early racial bias. Using a gaze-following paradigm, we investigated whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…However, the present results are compatible with a recent comparison of bilingual and monolingual infants’ gaze‐following behavior. Singh, Quinn, Xiao, and Lee (2019) demonstrated similarity in basic gaze‐following behavior in monolingual and bilingual groups, using a similar paradigm at 18 months. Similarly, Schonberg, Sandhofer, Tsang, and Johnson (2014) reported that there were no differences between monolingual and bilingual 3‐ and 6‐month‐olds looking patterns when viewing faces, objects, and complex scenes.…”
Section: Discussionmentioning
confidence: 96%
“…However, the present results are compatible with a recent comparison of bilingual and monolingual infants’ gaze‐following behavior. Singh, Quinn, Xiao, and Lee (2019) demonstrated similarity in basic gaze‐following behavior in monolingual and bilingual groups, using a similar paradigm at 18 months. Similarly, Schonberg, Sandhofer, Tsang, and Johnson (2014) reported that there were no differences between monolingual and bilingual 3‐ and 6‐month‐olds looking patterns when viewing faces, objects, and complex scenes.…”
Section: Discussionmentioning
confidence: 96%
“…In a social learning task in which 18‐month‐olds were cued to follow the gaze of own‐ and other‐race adults, monolingual infants exhibited an own‐race bias, favoring models of their own race over other‐race models. In contrast, bilingual infants demonstrated equal treatment of own‐ and other‐race models, although neither group had encountered the other race involved (Singh, Quinn, Xiao, & Lee, 2019).…”
Section: Effects Of Bilingualism On the Nature Of Perceptual Development And Learningmentioning
confidence: 99%
“…In more direct measures of race bias, 3‐ to 4‐year‐old bilingual children demonstrated less implicit racial bias than monolingual children of the same age, although neither group had any exposure to the other race involved (Singh, Quinn, Qian, & Lee, 2020). As with linguistic tasks, where bilingual infants are sensitive to sounds they have never encountered (e.g., Singh, 2018; Singh et al, 2017), bilingual openness extends to social groups never before encountered (Singh et al, 2019; Singh, Quinn, et al, 2020; Singh, Tan, et al, 2020). The precise links among bilingual exploratory behaviors, linguistic perception, and social openness remain to be determined through further empirical study.…”
Section: Effects Of Bilingualism On the Nature Of Perceptual Development And Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present results are compatible with a recent comparison of bilingual and monolingual infants' gaze-following behavior. Singh, Quinn, Xiao, and Lee (2019) demonstrated similarity in basic gaze-following behavior in monolingual and bilingual groups, using a similar paradigm at 18 months. Similarly, Schonberg, Sandhofer, Tsang, and Johnson (2014) reported that there were no differences between monolingual and bilingual 3-and 6-month-olds looking patterns when viewing faces, objects and complex scenes.…”
Section: Discussionmentioning
confidence: 84%